Chinese medicine, Gui Lu Er Xian Jiao – related serous retinal detachment 2nd to circumscribed choroidal hemangioma a case report - Hsin Hui Huang; Shiuh-Liang Hsu; Shwu-Jiuan Sheu (American Journal of Ophthalmology Case Reports, 2021)
Purpose: Circumscribed choroidal hemangioma is a rare condition where there is development of benign vascular tumors, and it generally appears in middle-aged adults. Here we report a case of Chinese medicine, Gui Lu Er Xian Jiao – related serous retinal detachment secondary to circumscribed choroidal hemangioma. Observations: A 55-year-old female, who had no remarkable ocular or medical history but has been taking a special Chinese compound medicine, Gui Lu Er Xian Jiao, for the past 2 years, presented with progressive blurred vision in the left eye for weeks. After serial ocular examinations, serous retinal detachment 2nd to circumscribed choroidal hemangioma was disclosed. Owing to the close timing association with medication history of Gui Lu Er Xian Jiao, we advised her to discontinue the Chinese medicine first. The serous retinal detachment resolved completely without any other management. Conclusions and Importance: The content of Gui Lu Er Xian Jiao has been reported to have angiogenesis effect, which possibly change the vascular permeability and induce the serous retinal detachment and therefore blurred vision in our patient. To the best of our knowledge, this is the first report on such relationship between Gui Lu Er Xian Jiao and serous retinal detachment 2nd to circumscribed choroidal hemangioma. The case report highlighted the importance of detailed history taking in the management of ocular diseases.